PENGARUH PENERAPAN E-SPT, PENGETAHUAN, SOSIALISASI, KESADARAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN MELAPORKAN PAJAK UMKM DI KOTA SEMARANG (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The purpose of this study was to examine and analyze the effect of the application of e-SPT, Tax Knowledge, Tax Socialization, Taxpayer Awareness and Tax Sanctions on Tax Reporting Compliance (Case Study on MSMEs in Semarang City). This study uses a survey method with quantitative data obtained by distributing research questionnaires directly and indirectly to 250 respondents as MSME taxpayers and using a Likert scale of 1-7. The data analysis technique used multiple linear regression analysis technique. The results of this study indicate that the application of e-SPT has a positive effect on tax reporting compliance and Tax knowledge has no effect on tax reporting compliance. Tax socialization has no effect on tax reporting compliance, Taxpayer awareness has a positive effect on tax reporting compliance and Tax Sanctions have a positive effect on tax reporting compliance.